Considerazioni sull’uso terapeutico di cannabis o delle ragioni della compassione (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
In the reconstruction of the therapeutic use of cannabis, this paper starts from the constitutional principle of health read through the reasons for the economic crisis and the implications of defensive medicine. Cannabis can play a crucial role in cases of severe pain, to allow patients a dignified life.
Keywords: therapeutic use of cannabis; compassionate use; defensive medicine; right to health; therapeutic freedom